Are risk minimization measures for approved drugs in Europe effective? A systematic review. Issue 5 (4th May 2019) - Artime, Esther; Qizilbash, Nawab; Garrido-Estepa, Macarena; Vora, Pareen; Soriano-Gabarró, Montse; Asiimwe, Alex; Pocock, Stuart
ABSTRACT: Objectives : The effectiveness of risk minimization measures (RMMs) requires evaluation. This study aims to evaluate the results of cross-sectional surveys assessing the effectiveness of RMMs in Europe (EU RM Surveys) and review the regulatory consequences. Methods : The authors searched for study reports and manuscripts of completed EU RM surveys in the EU PAS Register, MEDLINE, and Google between 01/2011 and 01/2018. Regulatory responses were extracted from Assessment Reports. Random effects models to combine proportions were used. Results : Twenty-four EU RM surveys were identified. Twenty-three studies targeted health-care professionals (HCPs). The pre-specified sample size was reached in 52% of studies. HCP participation was 5% defined as completers/invited and 89% for completers/eligible. Receipt of materials was recalled by 60% of HCPs and 77% of items scored knowledge >60%. Eight studies targeted patients/caregivers. The pre-specified sample size was reached in only two. Participation was 93%, defined as completers/eligible. Materials were received by 50–80% of patients and read by over 90%. Patients only scored knowledge >60% in 38% of items. Further action was requested by regulators in 59% of studies. Conclusion : Surveys are necessary to evaluate many RMMs. Challenges remain in the design, conduct, and reporting of these studies which may benefit from the use of standard definitions and further guidance on reporting. EU PAS Register : http://www.encepp.eu/encepp/viewResource.htm?id=23435